THE ELECTION COMMISSION OF INDIA'S (ECI) POWERS AND LEGAL FRAMEWORK By Mr. Shubhank Khare PhD Research Scholar (Law), Jagran Lakecity University, Bhopal, Madhya Pradesh ABSTRACT The Election Commission of India (ECI) plays a pivotal role in ensuring th (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The Election Commission of India (ECI) plays a pivotal role in ensuring the conduct of free, fair, and transparent elections in the world's largest democracy. Established under Article 324 of the Indian Constitution, the ECI is endowed with broad powers to supervise, direct, and control electoral processes across the nation. This paper examines the legal framework and powers vested in the ECI, exploring key constitutional provisions, statutory mandates, and operational mechanisms. Article 324, the Representation of the People Acts of 1950 and 1951, and the Delimitation Commission Act of 2002 form the cornerstone of the ECI's authority. The paper delves into the ECI's functions, such as the preparation and revision of electoral rolls, regulation of election conduct, and implementation of the Model Code of Conduct (MCC). It also highlights the Commission's role in promoting electoral reforms, voter education, and awareness. Despite its extensive powers, the ECI faces significant challenges, including allegations of bias, electoral malpractices, and technological and logistical hurdles. The paper discusses these challenges and the Commission's ongoing efforts to address them through reforms and technological innovations. Recent developments in electoral reforms, cybersecurity measures, and initiatives to increase voter participation are also explored. The study underscores the ECI's crucial role in safeguarding the democratic process in India and emphasizes the need for continuous improvement to meet emerging challenges. This comprehensive analysis provides valuable insights into the ECI's legal framework and operational dynamics, contributing to a deeper understanding of its pivotal role in India's democracy.